URINARY BLADDER FOREIGN BODY: A CASE REPORT - Parambang, Santi Ratnalia; Priyosantoso, Bacilius Agung (Indonesian Urological Association, 2023)
ABSTRACT Objective: This study aims to knowing the causes and symptoms is very important in determining the management. Case(s) presentation: A 44-year-old man came to the urology clinic with the chief complaint of painful urination after inserting an electric cable 1 meter long and 1 cm in diameter through the urethra 2 days earlier. The patient was then subjected to cystoscopy and removal of the cable using grasping forceps. Discussion: Urinary system foreign bodies can be caused by stimulation when the patient is conscious or under the influence of alcohol, mental disorder, curiosity to medical procedure (iatrogenic). Diagnosis of foreign bodies is based on history, physical examination and supporting examinations in the form of plain abdominal x-rays, ultrasound to CT-Scan. Removal of foreign bodies is adjusted to the type, size and location of foreign bodies in the urinary tract. Conclusion: Recognition of urinary system foreign bodies is very important. The various types of foreign bodies are a challenge for urologists. The selection of an appropriate operative intervention with low complications gives a good prognosis. Keywords: Foreign body, electrical wire, bladder, cystoscopy.